Different geomorphic processes control suspended sediment and bedload export from glaciers - Ian Delaney; Frédéric Lardet; Matt Jenkin; Davide Mancini; Stuart N. Lane (Nature Communications)
Abstract Ongoing cryospheric change has modified sediment export from glacierized catchments substantially, with significant implications for ecosystems and downstream users, notably hydropower companies. Sediment is exported either as finer sediment in suspension or as coarser bedload with intermittent contact between sediment and the bed. To date, the difficulty in observing subglacial bedload transport limits the understanding of the physical processes associated with evacuating bedload compared with suspended load. We elucidate the factors controlling sediment export by inverting a physically-based numerical model of subglacial sediment production and sediment transport with suspended sediment and continuous bedload discharge records from an Alpine glacier. Comparable quantities of suspended sediment and bedload are exported, and model results suggest that both rely on the availability of sediment for transport. Yet, bedload export in subglacial channels also depends on particular hydraulic conditions, notably channel shape and hydraulic roughness. This makes exporting bedload-sized particles inefficient compared to fine-grained sediment. As a result, subglacial hydraulics should be explicitly considered when examining bedload export processes, and suspended and bedload transport should be considered separately. Inefficient bedload evacuation by melt water implies that glacial erosion may only continue when non-fluvial mechanisms evacuate sediment, such as sediment entrainment into the ice.